Giovanni Falcone in front of the mafia. An unpublished interview (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The Storia e Memoria section of this issue offers an unpublished document: the interview with Giovanni Falcone collected by Chiara Lupani and Paola Monzini in 1988, at that time students working on an undergraduate thesis on the Sicilian mafia. The text is introduced by Chiara Lupani’s testimony who vividly traces the journey-research to Palermo that she conducted with her friend-colleague Paola Monzini, who unfortunately passed away in 2017. From Lupani’s reconstruction and from the profound and precise words shared by Falcone in the course of the interview, the value of the oral source in the study of the mafia clearly emerges.
Keywords: interview, Sicilian mafia, Palermo, Falcone.